Cross sections for single electron capture, transfer ionization and direct ioniza-tion in Li3+- Ne collisions - Luna, H. (2012)
Multiple ionization cross sections of Ne atoms are reported for Li 3+ impact in the energy range of 2 to 5.8MeV. The neon ionization cross sections were separated into three collision channels, namely; direct ionization (DI), single capture (SC) and transfer ionization (TI). The direct ionization data is compared to CDW-EIS calculations as well as to other projectiles with charge state q 3+. The single capture is compared to a modified Bohr-Lindhard semi classical model.